PAC1R agonist maxadilan enhances hADSC viability and neural differentiation potential. Issue 5 (22nd January 2016) - Guo, Xiaoling; Yu, Rongjie; Xu, Ying; Lian, Ruiling; Yu, Yankun; Cui, Zekai; Ji, Qingshan; Chen, Junhe; Li, Zhijie; Liu, Hongwei; Chen, Jiansu
Abstract: Pituitary adenylate cyclase‐activating polypeptide (PACAP) is a structurally endogenous peptide with many biological roles. However, little is known about its presence or effects in human adipose‐derived stem cells (hADSCs). In this study, the expression of PACAP type I receptor (PAC1R) was first confirmed in hADSCs. Maxadilan, a specific agonist of PAC1R, could increase hADSC proliferation as determined by Cell Counting Kit‐8 and cell cycle analysis and promote migration as shown in wound‐healing assays. Maxadilan also showed anti‐apoptotic activity in hADSCs against serum withdrawal‐induced apoptosis based on Annexin V/propidium iodide analysis and mitochondrial membrane potential assays. The anti‐apoptotic effects of maxadilan correlated with the down‐regulation of Cleaved Caspase 3 and Caspase 9 as well as up‐regulation of Bcl‐2. The chemical neural differentiation potential could be enhanced by maxadilan as indicated through quantitative PCR, Western blot and cell morphology analysis. Moreover, cytokine neural redifferentiation of hADSCs treated with maxadilan acquired stronger neuron‐like functions with higher voltage‐dependent tetrodotoxin‐sensitive sodium currents, higher outward potassium currents and partial electrical impulses as determined using whole‐cell patch clamp recordings. Maxadilan up‐regulated the Wnt/β‐catenin signalling pathway associated with dimer‐dependent activity of PAC1R, promoting cell viability that was inhibited by XAV939, and it also activated the protein kinase A (PKA) signalling pathway associated with ligand‐dependent activity of PAC1R, enhancing cell viability and neural differentiation potential that was inhibited by H‐89. In summary, these results demonstrated that PAC1R is present in hADSCs, and maxadilan could enhance hADSC viability and neural differentiation potential in neural differentiation medium.